2020
DOI: 10.1002/essoar.10503309.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abiotic drivers of a deep cyanobacteria layer in a stratified and eutrophic lake

Abstract: Harmful algal blooms (HABs), in particular those consisting of the cyanobacteria \textit{Microcystis}, are becoming increasingly more common across the globe. Despite the growing body of evidence that suggests vertical heterogeneity of \textit{Microcystis} can be a precursor to HAB formation, the abiotic drivers of vertical distribution of \textit{Microcystis} are poorly understood in the field environment. The prediction of subsurface cyanobacteria is also pertinent because subsurface concentrations are not e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Using a Bayesian biophysical model with a high‐frequency dataset, Del Giudice et al ( 2021 ) were able to quantitatively show that quiescent conditions are not enough: High surface water temperatures and high irradiation are also necessary for bloom formation. Recently, it has been suggested that vertical heterogeneity (i.e., subsurface peaks) of M. aeruginosa concentration is an important precursor to Microcystis surface bloom formation (Seegers et al, 2015 ; Xiao et al, 2018 ; Wilkinson et al, 2019 ; Taylor et al, 2021 ). Therefore, it is reasonable to assume improving models for the drivers of M. aeruginosa vertical distributions will likely lead to improved predictions of HAB timing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a Bayesian biophysical model with a high‐frequency dataset, Del Giudice et al ( 2021 ) were able to quantitatively show that quiescent conditions are not enough: High surface water temperatures and high irradiation are also necessary for bloom formation. Recently, it has been suggested that vertical heterogeneity (i.e., subsurface peaks) of M. aeruginosa concentration is an important precursor to Microcystis surface bloom formation (Seegers et al, 2015 ; Xiao et al, 2018 ; Wilkinson et al, 2019 ; Taylor et al, 2021 ). Therefore, it is reasonable to assume improving models for the drivers of M. aeruginosa vertical distributions will likely lead to improved predictions of HAB timing.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous field study, statistical methods were used to elucidate the reliance of Microcystis ‐dominated algal vertical distributions on lake thermal stratification variables (Taylor et al, 2021 ). Following the protocol discussed in Vinatier et al ( 2011 ), which suggests using statistical and mechanistic models in an iterative manner to uncover forcings of spatial heterogeneity, we propose a mechanistic model to analyze the effects of hydrodynamic and biological processes underlying the spatial patterns observed in the previous field study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation